Pendampingan Satuan Pendidikan Untuk Percepatan Implementasi Kurikulum Merdeka (IKM) SD Negeri 139 Kecamatan Lais dan Batik Nau - Roni Saputra; Deffri Anggara; Novi Lestari; Indra Utama (Jurnal Dehasen Untuk Negeri, 2023)
The launch of the independent teaching platform is in addition to supporting curriculum implementation. The launch of the independent teaching platform is not only to support the implementation of the independent curriculum in driving schools, but can also be used by all educators and education staff in educational units that have not yet become driving schools. Because the independent curriculum is the choice of schools in implementing the curriculum in educational units. So in general the Merdeka Teaching platform is a technology platform provided to support teachers so they can teach better, improve their competencies, and develop their careers. Lecture on “Education Unit Assistance Society for Accelerating Implementation of Independent Curriculum (IKM)”. Presenters consisting of 5 people took turns explaining the Implementation of the Independent Curriculum (IKM). The Merdeka Mengajar platform has many benefits that can help improve teacher competence in terms of transferring knowledge to students. The Merdeka Mengajar Platform can be used as a tool that can help teachers work so that learning objectives can be obtained and measurable.